Exploration of Patients’ Perspective on Telerehabilitation in Physiotherapy: What are Potential Facilitators and Barriers? - Marco Stahn; Anne-Kathrin Rausch (physioscience, 2026)
Abstract Telerehabilitation (TR) has emerged as a significant development in physiotherapy care. While research has examined physiotherapists’ perspectives on TR in Germany, patients’ experiences and views remain understudied. Previous research has primarily examined physiotherapists’ perspectives on TR; this study complements it by exploring the patients’ perspective, including satisfaction, barriers and facilitators. A qualitative study was conducted using individual and focus group interviews in 10 purposefully recruited patients with experience in TR-based physiotherapy. Data were analyzed using conventional content analysis, focusing on use patterns, satisfaction levels, and factors influencing TR adoption. Patients demonstrated high acceptance of TR, reporting positive experiences in establishing therapeutic relationships through digital means. Key facilitators included technical accessibility, professional digital platforms, and enhanced flexibility in care delivery. Primary barriers encompassed concerns about data security, technical infrastructure limitations, and preferences for hands-on treatment in specific conditions. A notable finding was that 7 out of 10 participants viewed TR as comparable to conventional therapy. Patients generally accept TR as a viable treatment option in German physiotherapy, particularly valuing its flexibility and integration into daily life.